Crisis Management in Tourism - Yarmola Kateryna M. (Bìznes Inform, 2022)
At the present stage of development of society, where everything is fleeting and changeable, the ability to respond flexibly and adapt to change is extremely important for the functioning of all sectors of the economy. The change of technologies, generations, the penetration of the information factor into all spheres of human life, all this form new requirements in the market. The modern tourism market needs innovative, creative, spontaneous, and most importantly – effective solutions that will allow enterprises to function with the minimum losses. The article is concerned with studying the features of the functioning of the tourism market in the face of constantly emerging risks and determining ways to overcome them. The main groups of risks that affect the tourism industry are considered. The dynamics of international tourist arrivals and the influence on it of various factors that led to the reduction of tourist activity in the world are examined. The main reasons for such negative changes, their consequences on the tourism market of individual countries and the world industry as a whole have been identified, the ways to counter them are analyzed. The article stipulates that the activities of the tourism sector largely depend on external factors that are practically beyond control. The greatest losses are caused by epidemics and diseases, among which the COVID-19 pandemic was the largest in terms of consequences, as the lack of response measures caused temporary stagnation in the industry, which required an accelerated search for solutions to problems. In addition, the article highlights the basics of crisis management in tourism and the stages of its implementation. According to the results of the study, the need to introduce risk management in the tourism industry is substantiated. Prospects for further research may be the grouping and systematization of risks, the development of methods to overcome them, as well as strategies for restoring and maintaining the tourism market.